If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = 5x + 2 Reorder the terms: -13 = 2 + 5x Solving -13 = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -13 + -5x = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 -13 + -5x = 2 + 0 -13 + -5x = 2 Add '13' to each side of the equation. -13 + 13 + -5x = 2 + 13 Combine like terms: -13 + 13 = 0 0 + -5x = 2 + 13 -5x = 2 + 13 Combine like terms: 2 + 13 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| x^2-6xy+y^2=6 | | 3x+x+21=-7 | | 3x=-159 | | 4x-7=271 | | x+45+45+35=360 | | 5(x-1)=3x+25 | | 11x+16=93 | | 344/2 | | 5sin(x-5)/4cos(x-5) | | 7x+1=61 | | -5(7+n)=-37-4n | | 4+4x=21x+12 | | (2x+1)sq-6=19 | | 4+49x=21x+12x | | 11x+9=11x-6 | | -11f=7(-1-2f)+5 | | 7x*9-2=5x-6 | | 9h+3=7h+5 | | 300+10x=y | | 4/7=21/(x-3) | | 10n=9n-9 | | x-0.7x=44 | | -4m=-8-5m | | 15(t-6)+3t=6(3t+4)-8 | | 4x+26+3x+14=180 | | 4x+5=1x-10 | | 2s+4=5(-4+2s) | | 3j/5-8J | | 5x-10=-2(x+3)-11 | | 7x+3=-2y+3 | | 2(2x-5)(6x+11)=0 | | x*.2=195 |